HUBUNGAN GRATITUDE DENGAN SUBJECTIVE WELL-BEING PADA DEWASA AWAL YANG MELAKUKAN FRUGAL LIVING - Faradilla, Isna; Viena, Yomima (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to examine the relationship between gratitude and subjective well-being among emerging adults who practice frugal living. A quantitative research method with a correlational approach was utilized in this study. The sample consisted of emerging adults aged 18–40 years who adopt a frugal living lifestyle, are employed in the Greater Jakarta area (Jabodetabek), and have a monthly income. Instruments used to measure subjective well-being included the Satisfaction with Life Scale (SWLS) and the Positive Affect and Negative Affect Scale (PANAS), while gratitude was measured using a modified version of The Gratitude-Six Item Form (GQ-6). Data analysis was conducted using the Pearson product moment correlation test. The results indicated a significant positive relationship between gratitude and subjective well-being among emerging adults practicing frugal living (r = 0.682, p < 0.05).